STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PADA USAHA UMKM SEDERHANA - Z, Muslimin; Zainuddin, Muhammad Zabir; Saputra, Muhammad Kepin (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2022)
The purpose of this study is to find out how the marketing strategy, namely the marketing mix which consists of products, prices, promotions and places applied by UMKM Sederhana, can increase sales of UMKM Sederhana chips products. This type of research is qualitative, namely research that is descriptive and tends to use narrative. Data collection techniques from this study used observation, interviews and documentation. The results of this study indicate that the marketing strategy carried out by UMKM Sederhana is to have quality products, the price is in accordance with the quality of the product, the distribution area is easily accessible and the promotions carried out have progressed by utilizing social media in sales which is currently very much needed because of the limited outside activities. outside the home due to the covid-19 pandemic so that many supermarkets are closed and the addition of two chip products from UMKM Sederhana, namely carrot chips and cashew cactus which have not been produced by many other businesses so that they are expected to help increase sales turnover from UMKM Sederhana.